Tax Collection Intensification In West Java Province - Zulfichar Kurniadi; Dyah Poespita Ernawati; Jona Bungaran Basuki Sinaga (Sean Institute, 2026)
The target for Motor Vehicle Tax (MVT) revenue in West Java Province consistently exceeded 100% from 2021 to 2024. However, in 2025, tax revenue reached only 92.02% of the target, amounting to IDR 5.67 trillion against the target of IDR 6.16 trillion. This decline highlights the need to intensify tax collection efforts to improve motor vehicle tax revenue. This study aims to analyze and describe the implementation of motor vehicle tax collection intensification in West Java Province and to identify an ideal tax intensification model for the province. The expected contribution of this research is to provide academic recommendations for strengthening motor vehicle tax collection in order to reduce the number of delinquent taxpayers and increase motor vehicle tax revenue. This study employed a qualitative method with a descriptive approach and was conducted at four research sites: the West Java Provincial Revenue Agency (Badan Pendapatan Daerah Provinsi Jawa Barat), the Regional Revenue Management Center (P3DW) of Bekasi City, Bogor Regency, and Bandung II Kawaluyaan. The findings indicate that strengthening and improving the tax intensification process is essential, including enhancing the tax database, strengthening tax collection procedures, improving tax supervision, increasing tax administration efficiency, and implementing better tax planning. In addition, the study recommends expanding the current tax intensification model implemented by the West Java Provincial Revenue Agency through stronger regulations for handling problematic taxpayer data, enhancing the capacity and role of human resources, and increasing the number of service units.